Highly Efficient Triplet Photosensitizers: A Systematic Approach to the Application of IrIII Complexes containing Extended Phenanthrolines. Issue 32 (4th July 2016) - Lu, Yue; McGoldrick, Niamh; Murphy, Frances; Twamley, Brendan; Cui, Xiaoneng; Delaney, Colm; Máille, Gearóid M. Ó; Wang, Junsi; Zhao, Jianzhang; Draper, Sylvia M.
Abstract: A series of Ir III complexes, based on 1, 10‐phenanthroline featuring aryl acetylene chromophores, were prepared and investigated as triplet photosensitizers. The complexes were synthesized by Sonogashira cross‐coupling reactions using a "chemistry‐on‐the‐complex" method. The absorption properties and luminescence lifetimes were successfully tuned by controlling the number and type of light‐harvesting group. Intense UV/Vis absorption was observed for the Ir III complexes with two light‐harvesting groups at the 3‐ and 8‐positions of the phenanthroline. The asymmetric Ir III complex (with a triphenylamine (TPA) and a pyrene moiety attached) exhibited the longest lifetime. Red emission was observed for all the complexes in deaerated solutions at room temperature. Their emission at low temperature (77 K) and nanosecond time‐resolved transient difference absorption spectra revealed the origin of their triplet excited states. The singlet‐oxygen ( 1 O2 ) sensitization and triplet‐triplet annihilation (TTA)‐based upconversion were explored. Highly efficient TTA upconversion ( Φ UC =28.1 %) and 1 O2 sensitization ( Φ Δ =97.0 %) were achieved for the asymmetric Ir III complex, which showed intense absorption in the visible region ( λ abs =482 nm, ϵ =50900 m −1 cm −1 ) and had a long‐lived triplet excited state (53.3 μs at RT). Abstract : Tapping into the triplet‐state ! A series of Ir III complexes, based on 1, 10‐phenanthroline featuring aryl acetylene chromophores, were prepared and investigated as triplet photosensitizers. Intense UV/Vis absorption was observed for the Ir III complexes, with two light‐harvesting groups at the 3‐ and 8‐positions of the phenanthroline. The asymmetric Ir III complex (with a triphenylamine (TPA) and a pyrene moiety attached) exhibited optimal properties. Its long lifetime contributed to its high upconversion, and near‐unity singlet oxygen, quantum yields.